2020
DOI: 10.21203/rs.3.rs-66640/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New in silico insights into the application of the (hydroxy)chloroquine with macrolide antibiotics co-crystals against the SARS-CoV-2 virus

Abstract: In this in silico study, the different pharmaceutical co-crystals based on the (hydroxy)chloroquine with the macrolide antibiotics (azithromycin, clarithromycin, or erythromycin A) was analyzed for the first time. These findings present a new molecular perspective and, therefore, suggest that the combination of (hydroxy)chloroquine/azithromycin, in the stoichiometric ratio of 1:1, as model co-crystals systems have less toxicity as well as is the most effective for inhibiting the new coronavirus SARS-CoV-2.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…37 As a result, it is important to note that the values extracted from RMSD (5R82 = 0.94 Ǻ / 3H5Y = 1.55 Ǻ) showed that the program used in this study is adequate for predicting the conformation that the co-crystallized ligands adopted experimentally within the viral M pro and RdRp of SARS-CoV-2. 12,13,38 The re-docking con gurations were maintained to perform the docking calculations of the drugs investigated as well as their metabolism fragments. All computed interaction energy results are exhibited in Table 1.…”
Section: Docking Results and Admetmentioning
confidence: 99%
See 3 more Smart Citations
“…37 As a result, it is important to note that the values extracted from RMSD (5R82 = 0.94 Ǻ / 3H5Y = 1.55 Ǻ) showed that the program used in this study is adequate for predicting the conformation that the co-crystallized ligands adopted experimentally within the viral M pro and RdRp of SARS-CoV-2. 12,13,38 The re-docking con gurations were maintained to perform the docking calculations of the drugs investigated as well as their metabolism fragments. All computed interaction energy results are exhibited in Table 1.…”
Section: Docking Results and Admetmentioning
confidence: 99%
“…36 The crystallographic M pro and RdRp structures used in this simulations were prepared according to our previous studies. 12,13,39 Based on this strategy, we also investigate the absorption, distribution, mechanism, excretion, and toxicity (ADMET) properties for antiviral target drugs and their by-products metabolic. Thereby, the acute toxicity and other relevant pharmacokinetics parameters can easily be obtained from a rat model-based admetSAR predictor (http://biosig.unimelb.edu.au/pkcsm/prediction).…”
Section: Computational Models and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2,[16][17][18] Due to the eminent urgency to fight this COVID-19 outbreak, researchers around the world have widely evaluated the effectiveness of diverse approved antiviral agents for this proposed. [1][2][3][19][20][21] Among these approved drugs, in particular, favipiravir (also known as T-705) is a compound analogous to guanine, which was developed with satisfactory activity against many RNA-polymerase viruses (e.g., Ebola, chikungunya, yellow fever, influenza, norovirus and enterovirus), [22][23][24][25][26][27] showed good clinical efficacy against coronavirus. 28,29 Although the highly mobile protons in the structure of favipiravir compounds has allowed for their tautomeric forms, 30 the interpretation of the spectroscopic properties of the tautomers has proven to be highly complex and difficult.…”
mentioning
confidence: 99%